2015
DOI: 10.1016/j.jebo.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Donations, risk attitudes and time preferences: A study on altruism in primary school children

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 38 publications
(21 reference statements)
3
39
0
3
Order By: Relevance
“…The Donation game has been utilized as an existence proof for the evolution of cooperation in highly mobile societies (Nowak and Sigmund, 2005). It can be described as a specific instantiation of the Prisoner's Dilemma (Suzuki and Kimura, 2013;Masuda, 2012;Uchida and Sigmund, 2010) and continues to be used for studying cooperation both theoretically (Tanabe et al, 2013;Masuda, 2012;Hilbe et al, 2013;Stewart and Plotkin, 2013;Uchida and Sasaki, 2013;Marshall, 2011Marshall, , 2009Nakamura and Masuda, 2012) as well as experimentally (Angerer et al, 2014;Sommerfeld et al, 2008). We confirm that the Donation game and the spreading of reputation can be used to sustain cooperation (Panchanathan and Boyd, 2003;Nowak and Sigmund, 2005).…”
Section: Introductionsupporting
confidence: 57%
“…The Donation game has been utilized as an existence proof for the evolution of cooperation in highly mobile societies (Nowak and Sigmund, 2005). It can be described as a specific instantiation of the Prisoner's Dilemma (Suzuki and Kimura, 2013;Masuda, 2012;Uchida and Sigmund, 2010) and continues to be used for studying cooperation both theoretically (Tanabe et al, 2013;Masuda, 2012;Hilbe et al, 2013;Stewart and Plotkin, 2013;Uchida and Sasaki, 2013;Marshall, 2011Marshall, , 2009Nakamura and Masuda, 2012) as well as experimentally (Angerer et al, 2014;Sommerfeld et al, 2008). We confirm that the Donation game and the spreading of reputation can be used to sustain cooperation (Panchanathan and Boyd, 2003;Nowak and Sigmund, 2005).…”
Section: Introductionsupporting
confidence: 57%
“…6 Uncertainty was furthermore reduced by the fact that the choice-list experiment was the third experiment conducted with these children. Therefore children had already experience with economic experiments (on social preferences; see Lergetporer et al, 2014, or Angerer et al, 2015 and receiving delayed payoffs (from previous experiments that were not related to intertemporal choice, though).…”
Section: Experimental Designmentioning
confidence: 99%
“…Ensuring comprehension is particularly challenging in the growing field of experiments with non-student subject pools such as low-educated persons, indigenous groups or children (see, for instance, Eckel et al, 2013;Angerer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that locally superior information on benefits made risk-averse individuals more likely to link to friends of friends. Angerer et al (2014) demonstrated that risk was closely related to prosocial behavior, but the relationship between risk preference and reciprocal altruism has not been clearly studied or explained. Rand and Epstein (2014) discussed altruism under extremely risky and costly conditions; however, the conclusion is difficult to generalize.…”
Section: Introductionmentioning
confidence: 99%